Collaborative Models for Inclusive Education: The Role of Communities in Supporting Learners with Diverse Needs - Ayesha Begum; Tasnia Islam; Istiarsyah Istiarsyah; Siti Aisyah Hanim (Yayasan Adra Karima Hubbi, 2026)
Background: Inclusive education increasingly demands collaborative approaches that extend beyond schools to involve families and communities. Learners with diverse needs often face academic, social, and emotional barriers that cannot be addressed through institution-centered strategies alone. Objective: This study aims to examine collaborative models for inclusive education, focusing on the role of communities in supporting learners with diverse needs and strengthening inclusive learning environments. Methods: The research employed a qualitative-dominant design integrating descriptive statistics and case-based analysis. Data were collected from teachers, school leaders, parents, and community representatives through interviews, observations, document analysis, and secondary institutional data. Inferential analysis was used to examine relationships between community collaboration and learner support outcomes. Results: The findings indicate that structured community collaboration significantly enhances learner participation, perceived inclusiveness, and access to support services. Strong partnerships characterized by shared decision-making, trust, and contextual responsiveness were associated with more effective inclusive practices. Case evidence further illustrates that community involvement contributes to learner confidence and classroom inclusivity. Conclusion: The study concludes that inclusive education is most effective when communities function as active partners rather than peripheral supporters. Collaborative models provide a sustainable framework for addressing learner diversity and advancing educational equity across diverse educational contexts globally today.